2011
DOI: 10.1152/japplphysiol.00064.2011
|View full text |Cite
|
Sign up to set email alerts
|

Early neural responses to strength training

Abstract: The neural adaptations that accompany strength training have yet to be fully determined. Here we sought to address this topic by testing the idea that strength training might share similar mechanisms with some forms of motor learning. Since ballistic motor learning is accompanied by a shift in muscle twitches induced by transcranial magnetic stimulation (TMS) toward the training direction, we sought to investigate if these changes also occur after single isometric strength training sessions with various contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
76
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(86 citation statements)
references
References 48 publications
9
76
0
1
Order By: Relevance
“…Substantial performance gains are exhibited within a single session, which simplifies the use of brain stimulation methods such as TMS to assess the neural underpinnings of adaptation (Carroll et al 2008). Moreover, the neural responses to ballistic motor training are similar to those observed after strength training (Selvanayagam et al 2011). Accordingly, the model provides a window into the mechanisms underlying an important physical attribute that often limits function in old age and in patients with neurological disorders.…”
Section: Task and Proceduresmentioning
confidence: 96%
“…Substantial performance gains are exhibited within a single session, which simplifies the use of brain stimulation methods such as TMS to assess the neural underpinnings of adaptation (Carroll et al 2008). Moreover, the neural responses to ballistic motor training are similar to those observed after strength training (Selvanayagam et al 2011). Accordingly, the model provides a window into the mechanisms underlying an important physical attribute that often limits function in old age and in patients with neurological disorders.…”
Section: Task and Proceduresmentioning
confidence: 96%
“…Our results are consistent with previous data from our laboratory, where twitch direction shifted significantly after training was performed at a distance of 90° away from the baseline twitch direction (Selvanayagam, et al, 2011). While some previous TMS studies, which involved repetitive ballistic thumb movements, reported that twitch directions shifted toward the training direction after 30 minutes of training at 180° away from baseline (Bütefisch et al, 2000;Bütefisch, et al, 2004;Classen, et al, 1998;Giacobbe, et al, 2011;Kaelin-Lang et al, 2005), we showed early neural adaptation occurred with a session of just 40 ballistic wrist contractions at 90° distance away from baseline (Selvanayagam, et al, 2011). The shift in twitch directions is likely to reflect the reweighting of connectivity among the forearm muscles to favour net force production in the training direction (Selvanayagam, et al, 2012a).…”
Section: Post Training Twitches In the Training Posturesupporting
confidence: 93%
“…In Chapter 5, we oriented the wrist into training and testing wrist postures and examined the resting twitch directions in these postures before and after a session of ballistic training. We sought to discover if ballistic contractions induce an adaptation toward the training direction in extrinsic or muscle-based reference frames, using the paradigm described by Selvanayagam et al (2011). We chose two wrist postures in our study so that a shift of twitch direction in one direction would imply extrinsic representation of use-dependent learning, whereas a shift in the other direction would imply a muscle-based representation.…”
Section: Pg 23mentioning
confidence: 99%
“…The experiment was designed based on a previous motor control study of Classen et al (6) who showed that short-term practice of directionspecific thumb movements can change the direction of stimulation-evoked thumb twitches. As in this earlier study, Selvanayagam et al (12) used suprathreshold transcranial magnetic stimulation (TMS) to induce directionally consistent movements of the forearm. After the initial test, subjects underwent three different strength training sessions involving either 1) brief contractions or 2) sustained ballistic contractions or 3) slow, sustained contractions.…”
mentioning
confidence: 99%
“…This could be done by identifying the neural mechanisms underlying the changes in twitch torque direction and, in the next step, inhibit their formation. As Selvanayagam and coworkers (12) have transferred a well-explored motor learning paradigm into the field of strength training, comparisons can be easily made. For instance, LTP was shown to play a role in the skill acquisition after repetitive thumb movements on the basis of pharmacological evidence (3).…”
mentioning
confidence: 99%